CALCULATION OF THE MULTI-BLADE ROTARY-FRICTION TOOL’S CUTTING CUPPED CUTTER TO STRENGTH IN THE ANSYS WB SURROUNDING - Sherov, Karibek; Rakishev, Asset; Sagitov, Almat; Donenbaev, Bakytzhan; Tussupova, Sayagul; Smakova, Nurgul; Imanbaev, Yernat; Mazdubay, Asylkhan (Journal of Applied Engineering Science, 2020)
The authors developed the design of a special multi-blade rotary-friction tool. The multi-blade rotary-friction tool is equipped with two cupped cutters – heating and cutting. The heating cupped cutter is made of medium-carbon structural steel of any brand, and the cutting cupped cutter is made of steel R6M5. The final formation of the treated surface and its quality is provided by the cutting cupped cutter. This article presents the results of the calculation of the strength of the cutting cupped cutter multi-blade rotary friction tool. As a result, the following were established: when processing steels 30HGSA cutting force components reach the maximum value than when processing materials 40HN2MA, St.45, and St.3c (calm); strength and rigidity of the cutting cupped cutter is sufficient for processing optimal cutting conditions: nsp = 1000 rpm; S = 0.42 mm / rot; t = 1.0 mm.